Enantiomeric separation of oxybutynin by recycling high‐speed counter‐current chromatography with hydroxypropyl‐β‐cyclodextrin as chiral selector. Issue 23 (13th October 2014) - Zhang, Panliang; Sun, Genlin; Tang, Kewen; Yang, Weijun; Sui, Guoqing; Zhou, Congshan
<x xml:space="preserve">Abstract</x> Recycling high‐speed counter‐current chromatography was successfully applied to the preparative separation of oxybutynin enantiomers. The two‐phase solvent system consisted of n‐hexane, methyl tert‐butyl ether, and 0.1 mol/L phosphate buffer solution (pH = 5.0) with the volume ratio of 6:4:10. Hydroxypropyl‐β‐cyclodextrin was employed as the chiral selector. The influence of factors on the chiral separation process, including the concentration of chiral selector, the equilibrium temperature, the pH value of the aqueous phase were investigated. Under optimum separation conditions, 15 mg of oxybutynin racemate was separated with the purities of both the enantiomers over 96.5% determined by high‐performance liquid chromatography. Recovery for the target compounds reached 80–82% yielding 6.00 mg of (R)‐oxybutynin and 6.15 mg of (S)‐oxybutynin. Technical details for recycling elution mode were discussed.